2010
DOI: 10.1016/j.jalz.2010.05.909
|View full text |Cite
|
Sign up to set email alerts
|

P1‐355: Mechanistic studies of antibody mediated clearance of tau aggregates using an ex vivo brain slice model

Abstract: Recent studies have shown that immunotherapy clears amyloid beta (Aβ) plaques and reduces Aβ levels in mouse models of Alzheimer's disease (AD), as well as in AD patients. Tangle pathology is also relevant for the neurodegeneration in AD, and our studies have shown that active immunization with an AD related phospho-tau peptide reduces aggregated tau within the brain and slows the progression of tauopathy-induced behavioral impairments. Thus, clearance of neurofibrillary tangles and/or their precursors may red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
5
8
0
Order By: Relevance
“…Importantly, this indicates that antibody-mediated Tau clearance takes place primarily within neurons. Previous data from our laboratory showed that antibodies were present in neurons of treated ani-mals and that the treatment resulted in clearance of phosphoTau but not total Tau (10), which we subsequently confirmed in other studies (11,12,19). Together, these prior studies suggest involvement of intracellular Tau antibodies in Tau clearance, and we now show in the primary Tg JNPL3 neuronal model that this pathway is necessary for removal of Tau.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Importantly, this indicates that antibody-mediated Tau clearance takes place primarily within neurons. Previous data from our laboratory showed that antibodies were present in neurons of treated ani-mals and that the treatment resulted in clearance of phosphoTau but not total Tau (10), which we subsequently confirmed in other studies (11,12,19). Together, these prior studies suggest involvement of intracellular Tau antibodies in Tau clearance, and we now show in the primary Tg JNPL3 neuronal model that this pathway is necessary for removal of Tau.…”
Section: Discussionsupporting
confidence: 88%
“…Recent results from our group have shown that Tau antibodies not only co-localize with intraneuronal pathological Tau but also with endosomal/lysosomal pathway markers (10,19). Sim-ilar findings have been observed by others utilizing antibodies for ␣-synuclein and A␤ (20 -22).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…For a number of years tau was considered to be purely intracellular. Sigurdsson et al reported antibodies inside neurons and proposed that antibody-mediated clearance of intracellular tau aggregates follows the lysosomal pathway [74,75]. Further studies have revealed that tau antibody uptake into neurons correlates well with tau levels.…”
Section: Targeting Taumentioning
confidence: 99%